Enhancement of Efficiency in an Ex Situ Coprecipitation Method for Superparamagnetic Bacterial Cellulose Hybrid Materials - Thaís Cavalcante de Souza; Italo José Batista Durval; Hugo Moraes Meira; Andréa Fernanda de Santana Costa; Eduardo Padrón Hernández; Attilio Converti; Glória Maria Vinhas; Leonie Asfora Sarubbo (Membranes, 2025)
Superparamagnetic magnetite nanoparticles (Fe3O4) have garnered considerable interest due to their unique magnetic properties and potential for integration into multifunctional biomaterials. In particular, their incorporation into bacterial cellulose (BC) matrices offers a promising route for developing sustainable and high-performance magnetic composites. Numerous studies have explored BC-magnetite systems; however, innovations combining ex situ coprecipitation synthesis within BC matrices, tailored reagent molar ratios, stirring protocols, and purification processes remain limited. This study aimed to optimize the ex situ coprecipitation method for synthesizing superparamagnetic magnetite nanoparticles embedded in BC membranes, focusing on enhancing particle stability and crystallinity. BC membranes containing varying concentrations of magnetite (40%, 50%, 60%, and 70%) were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and vibrating sample magnetometry (VSM). The resulting magnetic BC membranes demonstrated homogenous dispersion of nanoparticles, improved crystallite size (6.96 nm), and enhanced magnetic saturation (Ms) (50.4 emu/g), compared to previously reported methods. The adoption and synergistic optimization of synthesis parameters—unique to this study—conferred greater control over the physicochemical and magnetic properties of the composites. These findings position the optimized BC-magnetite nanocomposites as highly promising candidates for advanced applications, including electromagnetic interference (EMI) shielding, electronic devices, gas sensors, MRI contrast agents, and targeted drug delivery systems.